2019
DOI: 10.1021/acsanm.9b00890
|View full text |Cite
|
Sign up to set email alerts
|

Near Infrared-to-Near Infrared Upconversion Nanocrystals for Latent Fingerprint Development

Abstract: The advantages of near infrared (NIR)-to-visible upconversion nanoparticles (UCNP) for latent fingerprint development have been previously documented. In the present study, the use of NIR-to-NIR UCNP, composed of β-NaYF4:2%Tm, 48%Yb, is evaluated for latent fingerprint analysis. Here, 976 nm illumination is used to generate 800 nm luminescent fingerprint images. NIR-to-NIR UCNP are demonstrated to have significant advantages over NIR-to-visible UCNP in developing latent fingerprints. NIR-to-NIR UCNP are signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 44 publications
0
41
0
Order By: Relevance
“…Travis W. Over the past 3 years, our research group has been focusing on using upconverting nanoparticles (UCNPs, β-NaYF4:Yb/Tm) to develop fingerprints. This effort was successful with oleic acid-capped near-infrared (NIR)-emitting UCNPs (Baride et al, 2019). More recently, we have been focused on developing a system for reading fingerprints with UCNPs and for altering the UCNP surface such that DNA within the fingerprint can be captured and examined.…”
Section: A Conceptual Framework For Constructing and Integrating Insect Thermal Profiles Into Death Investigations Nij Award #: 2016-dn-bmentioning
confidence: 99%
“…Travis W. Over the past 3 years, our research group has been focusing on using upconverting nanoparticles (UCNPs, β-NaYF4:Yb/Tm) to develop fingerprints. This effort was successful with oleic acid-capped near-infrared (NIR)-emitting UCNPs (Baride et al, 2019). More recently, we have been focused on developing a system for reading fingerprints with UCNPs and for altering the UCNP surface such that DNA within the fingerprint can be captured and examined.…”
Section: A Conceptual Framework For Constructing and Integrating Insect Thermal Profiles Into Death Investigations Nij Award #: 2016-dn-bmentioning
confidence: 99%
“…For effective fingerprint imaging in full room light, NIR-to-NIR UCNP can be used, which is significantly brighter than NIR-to-visible UCNP (Figure 7). Images obtained at 800 nm suffer less from the background signal noise interference on substrates; this is because numerous inks cannot absorb at the 800 nm emission wavelength of NIR-to-NIR UCNP 60 .…”
Section: Latent Fingerprintingmentioning
confidence: 99%
“…Figure 7. Latent fingerprints developed with NIR-to-NIR (top row) and NIR-to-visible (bottom row) UCNP60 . Images reproduced from the references with permission.…”
mentioning
confidence: 99%
“…This process has been utilized in varied applications such as forensic and in situ biological imaging, temperature and mechanical stress sensing, as well as solar energy generation. [ 1–5 ] TTA‐UC has gained great attention because it can proceed efficiently at low threshold intensities of incident incoherent light at or below 100 mW cm −2 . [ 1,6,7 ] This phenomenon was first discovered in single molecules of anthracene and phenanthrene as early as 1962, [ 8 ] continued research has produced increasingly efficient TTA‐UC systems and revealed the ease of tuning optical properties in multicomponent systems.…”
Section: Introductionmentioning
confidence: 99%